The Effect of Organic Chemicals on Children's Room Equipment Elements on Parents' Preferences - Kemal YILDIRIM; Hakan YILMAZ; Betül HUYUGÜZEL (Gazi Üniversitesi Fen Bilimleri Dergisi, 2020)
In this study, it was aimed to determine whether parents of different ages, genders and educational levels living in Ankara have knowledge about the harmful effects of organic chemicals spreading from children's room equipment elements on human health. The questionnaire, developed for this purpose, was applied to 205 people selected by random method. As a result, it was determined that the parents did not have enough information about the organic chemicals coming out of the children's room equipment elements. Regarding the subject, it is seen that the participants aged 25-45 have less knowledge than the older people of 46 and above, while the secondary students have less knowledge than the higher education. However, no significant difference was found between the evaluations of participants with different genders in general. As a result, informing and raising awareness of users on this subject may enable the producer sector to reduce the use of materials that negatively affect human health.